The Role of Secondary Prevention in Modern Oncology: Current Trends in Screening for Breast, Colorectal and Cervical Cancer - Kwiatkowska, Aleksandra; Kosikowska, Aleksandra; Król, Adrianna; Gewald, Maja; Sobczak, Julia; Tołkacz, Aleksandra (Journal of Education, Health and Sport, 2026)
Introduction: Cancer is a leading cause of death worldwide, with breast, colorectal, and cervical malignancies accounting for a significant portion of the global oncological burden. The success of organised screening programmes is contingent on two factors: clinical efficacy and population participation rates. Aim: The aim is to evaluate the clinical importance and efficacy of screening programmes for breast, colorectal, and cervical cancers. Methods: A narrative review of literature from 2016–2025 was conducted via PubMed and Google Scholar. Key words used: 'screening', 'mammography', 'colonoscopy', 'FIT', 'cytology', 'HPV testing', 'prevention'. Results: Participation in mammography programmes has been demonstrated to reduce breast cancer mortality rates by 41–49%. For colorectal cancer, colonoscopy has been shown to reduce mortality up to 67%, while biennial FIT reduces it by 40%. In the context of cervical cancer, primary HPV testing offers superior sensitivity in comparison with conventional cytological analysis. Psychosocial barriers and false-positive results remain significant challenges across all programmes. Conclusion: The organised screening of patients is of vital importance in the diagnosis and treatment of the disease. The promotion of public education and the implementation of less invasive methods are pivotal in enhancing population adherence and reducing global cancer mortality.